Towards social change : essays on dalit literature - Sankar Prasad Singha (ed.); Indranil Acharya (ed.) (Orient Blackswan, 2014)
Papers presented at the conference on Translating Dalit Literature: Problems and Prospects, held at Vidyasagar University during 23-24 March 2010.